Sistem Pengukuran Daya Mekanik Penggerak Rotary Friction Welding Menggunakan Sensor Strain Gauge Pada Iron Holder Belt - Hambra Hidayatullah; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Rotary friction welding is a type of welding that belongs to the solis state type where welding does not require filling material to perform welding. This study aimed to measure the mechanical power of the rotary friction welding machine drive engine, before welding, during welding, and after welding using a strain gauge sensor attached to the stretch rod, for motor speed measured using an optocoupler sensor, the measurement process. This mechanical power included the design process, design, calibration settings, and testing of stretch rods. The stretch rod was installed as a substitute for the iron holder belt with the dimensions of the stretch rod 200 mm x 30 mm x 25 mm, for the thickness of the stretch rod where the strain gauge sensor is attached was 5 mm. The sensor used for reading the magnitude of the stretch on the stretch rod was the 120 ohm strain gauge, the speed read on the optocoupler was directly proportional to the amount of strain read on the strain gauge. In the welding process, a pressure of 2 bar to 4 bar is applied which will result in heat on the objects that rub against the object until it reaches the forging temperature of the object and a pressure of 6 bar is given as the forging pressure for weldingthe amount of mechanical power will be obtained by converting the torque, strain, and engine speed data obtained. Keywords: Friction Welding, Mechanical Power, Strain Gauge Sensor.